(untitled) (Research, Society and Development, 2025)
Electronic cigarettes (ECs), also known as "vapes," can cause negative effects on the oral cavity, including significant periodontal and dental changes, oral mucosal effects, changes in the microbiota and salivary glands, and impaired wound healing. The objective of this study was to analyze, synthesize, and discuss the main impacts of e-cigarettes on the oral cavity. Therefore, an integrative literature review was conducted in the PubMed databases via MEDLINE, PubMed Central, SciELO, and LILACS, in response to the guiding question: "What are the effects of e-cigarettes on the oral cavity?" Nine articles were eligible, highlighting the potential for e-cigarette use as a cause of deleterious effects on the oral cavity, such as periodontitis, caries, dysbiosis, oral mucosal lesions, and xerostomia. In addition to the damage caused to the oral cavity, e-cigarettes can cause cardiovascular and pulmonary diseases. It is therefore essential for dentists to understand the impacts of e-cigarette use on the oral cavity in order to make an accurate diagnosis, provide patient guidance, and encourage them to quit smoking. Evidence-based knowledge of the harmful effects on the oral cavity is essential for raising awareness and implementing preventive measures through public policies and continuing education.